Does the perception of red tape affect the emotional labor of frontline retail staff in China? A post-COVID-19 era. - Qin Qiang; Kaixin Wang; Jianxin Lai (PLoS ONE)
Red tape denotes valid rules or procedures that contribute nothing to achieving an organization's goals. How red tape affects corporate employees' emotional labor has received little attention. Therefore, this study recruited retail staff from Beijing after the COVID-19 pandemic, assessing the roles of negative emotions and customer orientation. Red tape negatively affected surface and deep acting among retail employees. Negative emotions mediated the relationships between red tape and surface and deep acting. Customer orientation moderated the relationship between negative emotions and surface acting as well as deep acting. Lastly, implications are provided for companies to promote employee emotional labor.While these measures were operationally necessary, their prolonged enforcement and administrative burden led employees to perceive them as bureaucratic obstacles rather than supportive regulations. Employees with high customer orientation may adopt alternative regulation strategies, such as cognitive reappraisal, instead of surface acting.